ОПТИМІЗАЦІЯ СТРИЖНЕВИХ МАТРИЧНИХ ФІЛЬТРІВ ВИСОКОГРАДІЄНТНИХ МАГНІТНИХ СЕПАРАТОРІВ - Толмачев, С.Т.; Ільченко, О.В. (Інститут електродинаміки НАН України, Київ, 2026)
The paper examines the theoretical and practical aspects of rod-structured matrix filters with double-periodic arrangement of elements, commonly employed in high-gradient magnetic separation technologies, with particular attention to comparative analysis and matrix optimization. An increasing number of studies on the development of highly efficient and lightweight high-gradient systems with reduced energy consumption is noted. The aim of the article is to substantiate and develop a method for optimizing matrix parameters according to the criterion of minimizing the specific energy of the magnetic field in the extraction zone, based on the calculation of local and effective force and energy characteristics of the magnetic field. The efficiency and universality of the proposed method are confirmed by a series of computational experiments with comprehensive consideration of factors influencing the quality of the final product. Specific examples demonstrate that the formation of an array of constant-magnetic-force lines (isodynes) serves as the principal means of investigating the extraction capacity of a matrix. A simple and effective approach to visualizing potential extraction zones is proposed in order to simplify the calculation of their areas. The application of the integral equation method with respect to the magnetization vector of matrix elements is substantiated, as it ensures maximum universality, simplicity, and accuracy in the analysis of complex double-periodic structures. The necessity of determining not only local but also effective magnetic field parameters in energy optimization is demonstrated. The dependence of matrix efficiency on the magnetic field intensity, rod shape and concentration, and their mutual arrangement is illustrated. The developed method is emphasized as being of a theoretical nature and is proposed as an effective complement to experimental analysis methods. It is shown that practical implementation of the method requires consideration of technological characteristics and constraints. Its value lies in the completeness and reliability of the additional information obtained on the basis of operational experience and high-quality experimental studies. References 20, figures 3, table 1.